Cell and Tissue Biology - Nikolsky, Nikolai N.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
The journal publishes papers on vast aspects of cell research, including morphology, biochemistry, biophysics, genetics, molecular biology, immunology. The journal accepts original experimental studies, theoretical articles suggesting novel principles and approaches, presentations of new hypotheses, reviews highlighting major developments in cell biology, discussions. The main objective of the journal is to provide a competent representation and integration of research made on cells (animal and plant cells, both in vivo and in cell culture) offering insight into the structure and functions of live cells as a whole. Characteristically, the journal publishes articles on biology of free-living and parasitic protists, which, unlike Metazoa, are eukaryotic organisms at the cellular level of organization.
Keywords: Cell biology; Cell Biology